Nuclear perfusion imaging for functional evaluation of patients with known or suspected coronary artery disease: the future is now. (July 2012) - Mc Ardle, Brian; Ziadi, Maria Cecilia; Ruddy, Terrence D; Beanlands, Rob S
Nuclear imaging, with both single-photon emission computed tomography and PET, has a well-established role in the assessment of patients with known or suspected coronary artery disease. There is a large body of evidence regarding the diagnostic accuracy and prognostic value of these modalities, however, they continue to evolve rapidly with advances in camera and tracer technology, as well as changes in imaging protocols to increase lab efficiency, improve image quality and to decrease radiation exposure to patients. Nuclear imaging also provides insights into atherogenesis at a molecular level and can be combined with other imaging modalities, providing both functional and structural data and complimentary information on the presence of coronary disease and its functional implications.